Analisis getaran dan kebisingan pada kamar mesin dan geladak penumpang kapal cepat Aluminium - Amalia Ika Wulandari; Suardi Suardi; Muhammad Yusuf Ismail (TURBO [Tulisan Riset Berbasis Online], 2021)
Ship vibration is part of the problem with ship dynamics. In addition to producing noise that disturbs the comfort of crew and passengers, engine structures and components can be damaged due to vibrations that are too high, resulting in material fatigue and material deformation. In order to avoid the damage that occurs and in order to improve the comfort of passengers and crew, shipbuilding must comply with vibration and noise standards. This study aims to analyze the value of vibration and the value of noise that arises on the aluminum fast boat as a result of excitation in terms of the main engine. Calculation of natural frequency and mode shapes is done using ship modeling with Finite Element Analysis Software. The excitation frequency of the main engine is 35.014 Hz. Based on the system's amplitude calculation, the values range from 3.273 x 10-7 to 2.703 x 10-6. Then the vibration standard values obtained are in the range of values from 0.253 to 2.093. Then, the noise radiation value obtained is in the range of 134,582 dB to 130,449 dB. All research results regarding vibration and noise standards in the engine room and passenger deck of aluminum ships obtained results that meet the standards, so it can be concluded that the ship's construction is safe from excessive vibration and noise.